1999
DOI: 10.2466/pr0.1999.85.3.1045
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Preference for Solitude Scale and Social Functioning

Abstract: The present study evaluated the hypothesis that those who prefer solitude should perceive social isolation as a positive experience. 391 university students volunteered to complete the Preference for Solitude Scale and a battery of social adjustment (e.g., Gough Creativity, Life Satisfaction, and Rosenberg Self-esteem) and maladjustment scales, e.g., Fenigstein Social Anxiety, Spielberger State Anxiety, and Social Isolation. Results provided partial support with correlations for solitude with social anxiety, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…For example, preference for solitude is considered as a benign disposition in emerging adulthood ( Bowker et al, 2017 ; Coplan, Ooi, et al, 2019 ). In support of this notion, researchers have found that preference for solitude is not associated with qualities of interpersonal relationships ( Nelson, 2013 ), loneliness ( Burger, 1995 ; Long et al, 2003 ), or social isolation ( Waskowic & Cramer, 1999 ). Furthermore, in a recent study examining perceived acceptability of others’ preference for solitude, participants rated solitude seeking to be highly acceptable (3.61; 1 = It’s really wrong , 4 = It’s perfectly okay ; Bowker et al, 2020 ).…”
Section: Dispositional Preference For Solitudementioning
confidence: 98%
“…For example, preference for solitude is considered as a benign disposition in emerging adulthood ( Bowker et al, 2017 ; Coplan, Ooi, et al, 2019 ). In support of this notion, researchers have found that preference for solitude is not associated with qualities of interpersonal relationships ( Nelson, 2013 ), loneliness ( Burger, 1995 ; Long et al, 2003 ), or social isolation ( Waskowic & Cramer, 1999 ). Furthermore, in a recent study examining perceived acceptability of others’ preference for solitude, participants rated solitude seeking to be highly acceptable (3.61; 1 = It’s really wrong , 4 = It’s perfectly okay ; Bowker et al, 2020 ).…”
Section: Dispositional Preference For Solitudementioning
confidence: 98%
“…The impact of preference for solitude was mixed, in that it was involved in enhancing as well as decreasing SWB. While some studies reported that preference for solitude enhanced SWB and was positively associated with loneliness ( Cramer and Lake (1998) ; Toyoshima & Sato, 2018 ), some studies did not find an effect of preference for solitude on SWB ( Long et al, 2003 ; Waskowic & Cramer, 1999 ); these findings make psychological concepts of preference for solitude unclear. From the results of this study, personal preferences included enjoyment of solitude, and evaluation of the productivity of solitude enhanced SWB; however, these effects were lower than the correlation of loneliness with a preference for solitude.…”
Section: Discussionmentioning
confidence: 97%
“…Preference for solitude is a factor explaining how aging individuals maintain their SWB even as their social interaction decreases; however, the results of previous studies on the same topic are not consistent. Some studies reported that preference for solitude did not correlate with life satisfaction ( Long et al, 2003 ; Waskowic & Cramer, 1999 ), while Toyoshima and Sato (2018) reported that preference for solitude was negatively associated with positive affect. A reason for this could be that preference for solitude is positively associated with loneliness, which is a hindrance for SWB because it is related to passivity in social interaction ( Burger, 1995 ).…”
Section: Preference For Solitude and Swbmentioning
confidence: 99%
“…Although it seems counterintuitive that people who report preferring time alone would not experience this time alone as more pleasant, there are a number of studies suggesting that the relation between preference for solitude and subsequent enjoyment of time alone is more complicated. For example, correlational studies tend to find that preference for solitude correlates with affect in much the same way that shyness and social anxiety do (i.e., positively associated with low self-esteem, negative affect, anxiety, and depression; Burger, 1995;Maes et al, 2016;Teppers et al, 2014;Waskowic & Cramer, 1999). These findings may be at least partly due to issues in operationalizing and measuring preference for solitude.…”
Section: Hypothesis 4: Does Preference For Solitude Moderate Change Imentioning
confidence: 99%
“…As mentioned earlier, this is even true among introverts (Zelenski et al, 2013), so there is reason to expect that the same may occur for those who prefer solitude. It is also true that preference for solitude is strongly correlated with other measures of social withdrawal (e.g., shyness, social avoidance), as well as outcomes related to social withdrawal (e.g., loneliness, depression, and anxiety) (Endo et al, 2017;Wang et al, 2013;Waskowic & Cramer, 1999). Although controlling for loneliness and social anxiety has in some cases found to attenuate or nullify these correlations (see Goossens, 2014 for a review), there remains conceptual overlap among these different motivations for solitude.…”
Section: Integrating Findings On Extraversion Preference For Solitudmentioning
confidence: 99%